In a Good Way: Reflecting on Humour in Indigenous Education - Leddy, Shannon (Journal of the Canadian Association for Curriculum Studies, 2018)
Humour is ubiquitous in Indigenous communities, and often provides some of the most memorable moments in our relationships with one another. In this article, I explore an instance of such humour backfiring in an educational situation, and reflect on whether humour was an appropriate response. After surveying some academic research in the area of humour in the classroom, as well as some of the works of several prominent Indigenous writers and comedians, I reflect on the importance of humour in Indigenous pedagogy. Drawing on this research, and moments from my own practice, I theorize that humour has three core pedagogical impacts. First, it has a humanizing affect, helping us to see one another more clearly, and to appreciate that we all have foibles, and areas of ourselves that require improvement. It is also a culturally relevant pedagogy, having been used for millennia as a mechanism of social order and of upholding community values in Indigenous communities. Finally, humour also has a soothing effect, especially in the face of grappling with difficult concepts and situations, and can ease the tensions that often arise in Indigenous education classrooms. Used judiciously, humour is a powerful tool for decolonization. While I do not presume to offer a prescription for the use of humour in the classroom, in reflecting on my own practice, I am increasingly convinced of its importance in Indigenous pedagogy, and I offer my reflections for the reader’s consideration.